2008
DOI: 10.4172/jpb.1000009
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics for Radiation-Induced Pathway Analysis from Proteomics and Microarray Data

Abstract: Functional analysis and interpretation of large-scale proteomics and gene expression data require effective use of bioinformatics tools and public knowledge resources coupled with expert-guided examination. An integrated bioinformatics approach was used to analyze cellular pathways in response to ionizing radiation. ATM, or ataxia-telangiectasia mutated , a serine-threonine protein kinase, plays critical roles in radiation responses, including cell cycle arrest and DNA repair. We analyzed radiation responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…In pancreatic adenocarcinoma, synergism between RRM2 siRNA and gemcitabine resulted in increased tumor apoptosis (28). RRM2 is a downstream target of the ATM-p53 pathway that mediates radiation-induced DNA repair (29) and silencing of RRM2 was found to enhance DNA damage as measured by histone γ-H2AX. Under DNA damage and Chk1 activation mediated by ATM and ATR, upregulation of RRM2 expression level coupled with its nuclear recruitment suggests an active role of RRM2 in the cellular process in response to DNA damage (30).…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic adenocarcinoma, synergism between RRM2 siRNA and gemcitabine resulted in increased tumor apoptosis (28). RRM2 is a downstream target of the ATM-p53 pathway that mediates radiation-induced DNA repair (29) and silencing of RRM2 was found to enhance DNA damage as measured by histone γ-H2AX. Under DNA damage and Chk1 activation mediated by ATM and ATR, upregulation of RRM2 expression level coupled with its nuclear recruitment suggests an active role of RRM2 in the cellular process in response to DNA damage (30).…”
Section: Discussionmentioning
confidence: 99%
“…Defective RR often leads to cell cycle arrest, growth retardation, and high mutation rate (8). The high level of RRM2 protein and RR activity in human nasopharyngeal cancer cells results in ionizing radiation resistance through enhancing damage repair during G 2 phase of the cell cycle (1). CHK1 is widely known as a DNA damage checkpoint signaling protein (9).…”
Section: Ribonucleotide Reductase (Rr)mentioning
confidence: 99%
“…2 is the only enzyme responsible for the reduction of ribonucleotides to their corresponding deoxyribonucleotides and a rate-limiting enzyme for the production of 2Ј-deoxyribonucleoside 5Ј-diphosphates (dNTP) required for DNA synthesis and repair (1)(2)(3). RR consists of RR1 (encoded by the Rrm1 gene) and RR2 (encoded by the Rrm2 and Rrm2b genes) subunits, and both proteins are required for enzymatic activity.…”
Section: Ribonucleotide Reductase (Rr)mentioning
confidence: 99%
“…Direct comparison of expression at both mRNA and protein levels can provide stronger evidences for the underlying changes. For example, the 2D-gel/MS proteomics study identified 412 and 771 proteins that potentially changed in response to radiation treatment in ATM (Ataxia Telangiectasia Mutated) mutated (ATM − ) and wild type (ATM + ) cells, respectively, while the gene microarray study identified 103 and 131 significantly changed genes in the two cells, respectively (54). Among those genes/proteins, only 13 were commonly identified, including RRM2, the catalytic subunit of ribonucleoside-diphosphate reductase (RR), a rate-limiting enzyme required for synthesis of dNDP and thus of DNA synthesis in human (55).…”
Section: Methodsmentioning
confidence: 99%
“…Pathway profiling also led to the identification of “purine metabolism pathway” that showed notable differences between radiation-treated vs. untreated ATM − and ATM + cells (Fig. 5a) (54). …”
Section: Methodsmentioning
confidence: 99%